Online social networks and security of their users: an exploratory study of students at the Faculty of humanities and social sciences Zagreb - Vrana, Radovan (Array, 2013)
The paper presents results from the research of students at the Faculty of humanities and social sciences in Zagreb, Croatia about their views and opinions about secure use of online social networks. The results indicate that most respondents are experiences users of online social networks ; however, they rarely change passwords in their online profiles and most of them have never had any education about online security in general and methods of protection of personal data on online social networks. Luckily, most of them have never suffered from breaking into their profiles on online social networks.